Movement ecology research to advance conservation of South America's grassland migratory birds - Jahn, Alex (2017)
South America is home to some of the largest, most diverse grasslands on the planet, providing critical habitat for numerous plants and animals and vital resources for millions of people. Yet, at the dawn of the 21st Century, South America´s grasslands are experiencing rapid, widespread and unprecedented impacts from activities such as pesticide use, drainage, urbanization, and conversion to industrial monocultures. In combination with the pervasive effects of global climate change, these impacts have the potential to ripple across grassland food webs in ways we still poorly understand. How do these impacts affect the behavior, ecology and population demographics of the numerous migratory birds that call these grasslands home? Given the historical lack of research on grassland birds across the New World, we know very little about how to best conserve them, much less which grassland migratory birds are currently impacted or likely will be in the near future. We argue that, by applying recent theoretical and technological advances in the field of movement ecology, rapid advances can be achieved in understanding grassland migratory birds in South America. We outline the current state of knowledge about grassland birds that migrate within South America, the main threats to their survival, and how the emerging field of movement ecology can contribute to understanding how to conserve and manage their populations. Only with information on the full annual cycle of these birds will we be able to formulate effective conservation and management plans to ensure the long-term viability of these unique species